Adrenal Insufficiency in Cystic Fibrosis: A Rare Phenomenon? - Sébastien Préville-Ratelle; Adèle Coriati; Aurélie Ménard; Isabelle Bourdeau; François Tremblay; Yves Berthiaume (Canadian Respiratory Journal)
Background. The prevalence of adrenal insufficiency (AI) in cystic fibrosis (CF) is unknown. The frequent use of glucocorticoids (inhaled or systemic) may induce the long-term suppression of the hypothalamic-pituitary-adrenal axis. Methods. We reviewed the results of adrenocorticotropic hormone (ACTH) stimulation tests done over a 10-year period to evaluate adrenal function in 69 CF patients of the CHUM CF clinic. Clinical characteristics of AI patients were compared to adrenal-sufficient (AS) patients. Results. AI was confirmed in 33 of the 69 CF patients. A higher rate of dysglycemia P=0.022 and of Aspergillus positive culture P=0.006 was observed in AI patients compared to AS patients. Weight, CFTR genotype, and pulmonary function were comparable between AI and AS patients. The use of systemic corticosteroids (SC) prior to the diagnosis of AI was observed in 42.4% of patients. Compared to AI patients without SC, SC-treated AI patients were older and had a higher rate of allergic bronchopulmonary aspergillosis. Conclusion. This study is the first to systematically examine the presence of AI in the largest cohort of CF patients studied to date with a prevalence of 8%. Patients treated with corticosteroids and those colonized with Aspergillus have a greater risk of AI.